Theoretical Model of the Relationship between Single Embryo Transfer Rate and Multiple Pregnancy Rate in Japan - Syuichi Ooki (Journal of Pregnancy)
The purpose of the present study was to examine the effect of single embryo transfer (SET) in assisted reproductive technology (ART) on the reduction of the multiple pregnancy rate. We also estimated the monozygotic (MZ) twinning rates according to the SET diffusion indirectly. A reverse sigmoid curve was assumed and examined using nationwide data of SET from 2007 to 2009 in Japan. The multiple pregnancy rate decreased almost linearly where the SET pregnancy rate was between about 40% and 80% of regression approximation. The linear approximation overestimated multiple pregnancy rates in an early period and underestimated multiple pregnancy rates in the final period. The multiple pregnancy rate seemed to be influenced by the improvement of the total pregnancy rate of ART in the early period and by the MZ twinning after SET in the final period. The estimated MZ twinning rate after SET was around 2%.